(3MGTjI Ydi TQM GdJgPjH aj GdefWbs - (3GdYdjej GdMeUj, jGSjf Hf Rjf GdOjf Hf CHj HcQ, J (B1061 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj NU HGdfWb fhY GdEfSGf GeG HYO ajbhd GdabjQ Edi QMeI QH GdYGdejf jGSjf hQCjJ Cf CMb cJGH CbdO LjOg OQQ GdbdGjO hCgOj Edi PNGjQg fajS GdahGFO TQM GdJgPjH ddEeGe GdNHjUjs
(3BNQgG (B:s
(3hbO TQM Pdc TjN GdESdGe aGQLY Edjg Cf TjJ (B( (3cPG (B) (3JaUjd GdebGd hdjcf gPG BNQ eG CQOfG GjQGOg aj gPg GdMhGTj hGdMeO ddg Ydi LejY GdCMhGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8 / 130s
(3eYLe GdeDdajf (B4 / 81s
(3NdGUI GdCKQ (B4 / 491s
(3gOjI GdYGQajf (B2 / 512s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs